Short-course treatment with ceftriaxone for leptospirosis: A retrospective study in a single center in Eastern France. Issue 3 (March 2015) - Faucher, Jean-François; Chirouze, Catherine; Hoen, Bruno; Leroy, Joël; Hustache-Mathieu, Laurent; Estavoyer, Jean-Marie
Abstract: Short-course (less than 7 days) antibiotic treatments have been rarely assessed in the management of leptospirosis. We analyzed the charts of patients hospitalized with confirmed and probable leptospirosis in a teaching hospital between 1994 and 2012. Of 89 patients with confirmed or probable leptospirosis, 21 patients (11 confirmed, 10 probable - 14 uncomplicated and 7 severe forms) admitted between 2001 and 2012 received ceftriaxone (1–2 g daily) for less than 7 days. Apyrexia was obtained within 2 days of treatment in all patients and no relapse was observed. These data support the hypothesis that short-course treatments of 3–6 days with ceftriaxone (1–2 g per day) may be an option in the treatment of uncomplicated and severe forms of leptospirosis responding quickly to therapy. This hypothesis deserves being confirmed in further clinical studies.